PENERAPAN PRINSIP ETIKA LINGKUNGAN PADA TEKNOLOGI REKAYASA GENETIK TANAMAN DAN REGULASI KEAMANAN PRODUK REKAYASA GENETIKA - Isna Rahma Dini; Hapsoh Hapsoh; Arnisa En Yuli (Pelantar Press, 2023)
Biotechnology activities related to genetic engineering in plants are currently developing rapidly. This is done to overcome several problems related to improving the quality of food crops as well as various obstacles encountered during crop cultivation. However, along with the development of transgenic plants, various environmental issues due to genetic engineering technology in plants have emerged. The perpetrators of genetic engineering technology development must of course continue to apply environmental ethics so that cases related to the development of genetic engineering products do not occur. Therefore, efforts are needed to apply environmental ethical principles to genetic engineering technology. Several principles of environmental ethics include (1) respect for nature; (2) The principle of moral responsibility (moral responsibility for nature); (3) cosmic solidarity; (4) compassion and concern for nature (caring for nature); (5) The principle of not causing damage (no harm principle); (6) Living simply and in harmony with nature; (7) The principle of justice; (8) The principle of democracy; (9) The principle of moral integrity. In addition to upholding the ethical principles of the environment, government regulations regarding the safety regulations for genetically engineered products must still be complied with in order to avoid the risk of negatively impacting these engineered products.